CHARACTERIZING THE BIOPHYSICAL PROPERTIES OF NORMAL AND CANCER NEURAL STEM CELLS - Kulseiit, Dana (Nazarbayev University School of Sciences and Humanities, 2022)
Cancer is one of the leading causes of deaths worldwide accounting for 10 million people deceases in 2020. Metastatic spreading is the key feature that makes cancer difficult to cure. Stiffness and adhesion of cancer cells were found to be altered during metastasis, leading to a hypothesis that these changes are correlated with their migrating ability. In this project, we explore whether there is a difference between normal and cancer cells based on their biophysical and biomechanical properties such as cell cycle and mitosis times, cell cross-sectional area, spindle length, and cortical stiffness. Drosophila melanogaster neuroblasts (NBs) were used as a model for this study. The results revealed that pins mutant and brat mutant NBs mitosis times are similar to wildtype in S2 medium, however pins mutant NBs have longer mitosis times in comparison to wildtype and brat mutant NBs in CGS. With regard to cell cycle times in S2 medium, there is no significant difference between wildtype and brat mutant neuroblasts. Additionally, pins mutant NBs turned out to be softer and smaller in size compared to wildtype and brat mutant NBs. Therefore, we concluded that depending on the type of cancer or mutation, the cells may display different biophysical and biomechanical properties in contrast to their wildtype counterpart. Keywords: Drosophila neuroblast, live cell imaging, atomic force microscopy.
Keywords: drosophila neuroblast; live cell imaging; atomic force microscopy; Type of access: Open Access; Research Subject Categories::NATURAL SCIENCES